My friends call me monster - Stine, R. L. (New York : Scholastic, 2009)
Michael Munroe learns to never trust a teacher that calls his students "Little Monsters" when he finds himself trapped in Horrorland after a lunch with the suspicious teacher.
My friends call me monster -- Enter HorrorLand -- Fear file.
3.5
5-8
Keywords: Amusement parks -- Juvenile fiction; Schools -- Juvenile fiction; Teachers -- Juvenile fiction; Amusement parks -- Fiction; Horror stories; Schools -- Fiction; Teachers -- Fiction; Amusement parks -- Fiction; Horror fiction; School stories; Teachers -- Fiction; Horror fiction